Advances in tissue engineering of nanocellulose-based scaffolds: A review. (15th November 2019) - Luo, Huize; Cha, Ruitao; Li, Juanjuan; Hao, Wenshuai; Zhang, Yan; Zhou, Fengshan
Highlights: We discussed the tissue engineering applications of nanocellulose-based scaffolds. We summarized methods to prepare scaffolds such as electrospinning and 3D printing. We highlighted the repairing and replacement of heart, liver and ophthalmology. We outlined the challenges and potentials of nanocellulose-based scaffolds. Abstract: Scaffolds based on nanocellulose (NC) have crucial applications in tissue engineering (TE) owing to the biocompatibility, water absorption, water retention, optical transparency, and chemo-mechanical properties. In this review, we summarize the scaffolds based on nanocellulose, including nanocrystalline cellulose and nanofibrillated cellulose. We compare four representative methods to prepare NC-based scaffolds, containing electrospinning, freeze-drying, 3D printing, and solvent casting. We outline the characteristics of scaffolds obtained by different methods. Our focus is on the applications of NC-based scaffolds to repair, improve or replace damaged tissues and organs, including skin, blood vessel, nerve, skeletal muscle, heart, liver, and ophthalmology. NC-based scaffolds are attractive materials for regeneration of different tissues and organs due to the remarkable features. Finally, we propose the challenges and potentials of NC-based TE scaffolds.